Notification of crop varieties and registration of germplasm : Tall fescue Variety Greenmaster2ho / Orchardgrass Variety Onnuri 2ho / Variety Lucky One - Lee, S.H.; Ji, H.C. (The Indian Journal of Genetics and Plant Breeding, 2016)
Tall fescue Variety Greenmaster2ho /Orchardgrass Variety Onnuri 2ho /Variety Lucky One